Investigation of groundwater circulation models in the Jiuquan Basin - Wang, Wenxiang; Yu, Shengbo; An, Yonghui; Li, Wenpeng; Cai, Yuemei; Shao, Xinmin; Wu, Xi; Cui, Huqun; Yin, Dechao; Wang, Xiaoyan (Frontiers in Environmental Science, 2025)
The Jiuquan Basin, with area of 6,800 square kilometers, located in the arid northwest of China, is a vital part of the Hexi Corridor. Investigating its groundwater circulation model is essential for understanding regional hydrogeological processes, sustainable water resource management, and ecological protection. This study, building upon previous research, utilizes hydrogeological surveys, hydrogeochemical analysis, isotope tracing (δD and δ18O) with sample size of 439, and radiocarbon dating (14C) with sample size of 45 to evaluate the groundwater flow systems and groundwater age distribution. Results reveal that groundwater primarily originates from meltwater from the Qilian Mountains and atmospheric precipitation, flowing from south to north. The central basin exhibits slower circulation and older groundwater, while the groundwater in the Heihe River mainstream and the Beida River Basin was relatively young due to the favorable conditions for recharge and discharge. The local meteoric water line (LMWL) is defined as δD = 6.02 × δ18O- 2.5. Based on isotopic and age data, the basin is divided into several secondary groundwater flow systems (SGFS). This work contributes valuable insight into arid-zone hydrodynamics and supports ecological and water management strategies in the Jiuquan Basin.